Primary Immunodeficiency Diseases: An Update on the Classification from the International Union of Immunological Societies Expert Committee for Primary Immunodeficiency - Al-Herz, Waleed; Bousfiha, Aziz; Casanova, Jean-Laurent; Chatila, Talal; Conley, Mary Ellen; Cunningham-Rundles, Charlotte; Etzioni, Amos; Franco, Jose Luis; Gaspar, H. Bobby; Holland, Steven M.; Klein, Christoph; Nonoyama, Shigeaki; et al. (Frontiers in Immunology, 2014)
We report the updated classification of primary immunodeficiencies compiled by the Expert Committee of the International Union of Immunological Societies. In comparison to the previous version, more than 30 new gene defects are reported in this updated version. In addition we have added a table of acquired defects that are phenocopies of primary immunodeficiencies. For each disorder, the key clinical and laboratory features are provided. This classification is the most up to date catalogue of all known primary immunodeficiencies and acts as a current reference of the knowledge of these conditions and is an important aid for the molecular diagnosis of patients with these rare diseases.